An Analysis of Simple Past Tense Errors in the Soul Sense with Silkina Podcast by Using the Surface Strategy Taxonomy - Nurmala, Ela; Rahayu, Ika; Sapari, Gingin Ginanjar; Rahayu, Rahmayanti (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2023)
The purpose of this study is to investigate the simple past tense errors found in the Soul Sense with Silkina Podcast. The study employed qualitative method with descriptive analysis. The data were collected from a podcast entitled Soul Sense with Silkina Podcast which consists 10 episodes of Soul Sense with Silkina Podcast. The data were analysed by applying the Surface Strategy Taxonomy proposed by Dulay. The result shows that there were four types of errors committed by the podcasters in using Simple Past Tense. Those types were Omission, Addition, Mis-formation and Mis-ordering. The total numbers of errors were 120 divided into Omission (23 errors), Addition (11 error), Mis-formation (82 errors), and Mis-ordering (4 errors). In other words, the highest amount of errors was Mis-formation with the percentage of 68.34%, while the omission was in the second place with the percentage around 19.17%. The third place was addition with the percentage around 9.16%, and the last was mis-ordering with the percentage around 3.33%.